HEALTH AND REHABILITATION GAMES FOR CHILDREN WITH DISTURBANCE OF THE FUNCTIONAL STATE OF THE DIGESTIVE SYSTEM IN THE COMPLEX REHABILITATION PROGRAM - Bakay, I.N.; Konstantinova, N.P.; Ivanova, O.S.; Semiryazhko, M.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to experimentally substantiate the effectiveness of the use of health-improving and rehabilitation games for children aged 5-6 years with functional indigestion. Methods and structure of the study. The developed comprehensive program of physical rehabilitation of children aged 5-6 years with a violation of the functional state of the digestive system was used, which consisted of adaptation, training and stabilization periods and included therapeutic exercises, hydrocolonotherapy, therapeutic massage, self-study. Results and conclusions. The developed comprehensive program of physical rehabilitation allowed to achieve a more effective improvement in the functional state of the digestive system, the clinical picture of the disease, and had a positive effect on the health of children with biliary dyskinesia.